2020
DOI: 10.2478/cejpp-2020-0008
|View full text |Cite
|
Sign up to set email alerts
|

Public policy responses to the spread of COVID-19 as a potential factor determining health results: a comparative study of the Czech Republic, the Russian Federation, and the Slovak Republic

Abstract: The goal of this paper is to identify critical factors in success/failure of public policies focusing on fighting the spread of COVID-19 pandemic using a sample of three countries from Central and Eastern Europe with different results regarding COVID-19 morbidity and mortality rates, namely the Czech Republic, the Russian Federation, and the Slovak Republic. Based on comprehensive literature review, three independent variables were worked out: the scope/scale of public policy anti-pandemic interventions, the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 11 publications
(9 reference statements)
1
11
0
Order By: Relevance
“…As the leading authority in our case countries, government-issued documents were analysed for our study. In contrast with a previously published review of international public health responses to the COVID-19 outbreak (23)(24)(25), our analytical strategy focuses on a small sample and applies the most similar stems design (26). Focusing on three conservative welfare states (27), which are highly populated, economically relevant, and geographically close, allows us to conduct an in-depth analysis and comparison.…”
Section: Methodsmentioning
confidence: 99%
“…As the leading authority in our case countries, government-issued documents were analysed for our study. In contrast with a previously published review of international public health responses to the COVID-19 outbreak (23)(24)(25), our analytical strategy focuses on a small sample and applies the most similar stems design (26). Focusing on three conservative welfare states (27), which are highly populated, economically relevant, and geographically close, allows us to conduct an in-depth analysis and comparison.…”
Section: Methodsmentioning
confidence: 99%
“…27 Russia also underestimated the epidemic for a long time and then undertook incoherent and half-hearted measures such as stopped importation of virus from China; but risks associated with importation of cases from Europe were underestimated. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Czech Republic and Slovak Republic introduced lockdowns before they had recorded any deaths 29 and made it mandatory for people to wear masks outside the home since beginning. 28 Slovak Republic achieved early and effective quarantine measures and Slovak citizens behaved more responsibly. 28 A study comparing public policy response in Czech Republic, Russia and Slovak Republic, reported that Slovak Republic was the best performer, Czech Republic was good performer and Russia was reported as a limited performer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common strategies to prevent nosocomial transmission include outlining a clear plan for providing essential services during the pandemic, with dedicated COVID-19 beds and units [55]; separation of healthcare facilities for the treatment of infected COVID-19 patients and non-COVID-19 patients and increasing intensive care bed capacity [56]. Given the similarity of measures introduced by governments, the results suggest that the success of measures to encourage compliance may be critical factors in containing the pandemic [57].…”
Section: The Prevention Strategiesmentioning
confidence: 99%